YIELD OF EARLY POTATOES IN THE CONDITIONS OF WESTERN SERBIA: Early poptato - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2025)
The goal of the research was to determine the variation in the yield of early potatoes in the conditions of western Serbia. During 2021 and 2022, the experiment was carried out at the site of KO Bogatić, the area of ​​the village of Belotić (65 m above sea level, chernozem), 44˚ 49’ N, 19˚ 32’ E. The research was set up with three potato varieties: one early (Colomba) and two medium early (Esmee and Memphis). The analysis of productive traits showed very significant differences (r<0.01) and (r<0.05) under the influence of the variety (factor G). The influence of the year (factor E) and the interaction of factors (E × G) on the examined productive traits of early potatoes were absent. The mid-early varieties Esmee and Memphis showed a significantly lower yield of early potatoes, compared to the early variety Colomba. A significant positive correlation was found between the yield of new potatoes and the number of tubers per plant (r = 0.78447, p<0.05). We can conclude that the Colomba variety, due to its early maturity and genetic predisposition, formed and bulking the tubers the fastest, which directly influenced the achievement of the highest yield of early potatoes.